Riddles in East Baltic and West Slavic Folktales - Pintāne, Inese (Tautosakos darbai, 2026)
Unlike riddle compilations, which typically present fixed questions and their answers with minimal information about the riddles’ origin or narrative function, folktales offer a rich context for gaining deeper insight into how riddles emerge, operate and acquire meaning. This study explores the prevalence and characteristics of riddles within a corpus of 1914 folktales from East Baltic and West Slavic traditions, specifically from Latvia, Lithuania, Poland, Czechia and Slovakia, focusing mainly on those written down in the 19th century and at the beginning of the 20th century. The study examines the functional, structural and procedural aspects of riddling as a narrative device, as well as the roles and genders of the participants involved. The findings are supported by a comprehensive table at the end of this study that lists all the riddling episodes identified within the given corpus of folktales. The study provides a detailed account of how riddles operate within these specific traditions and reveals that riddles are a relatively rare phenomenon in the folktales of these peoples. In addition, the study demonstrates that there are no substantial differences in folktale riddles between East Baltic and West Slavic traditions.
Keywords: folktales; riddles; Baltic; Slavic